Nuclear weapons ; a very short introduction - Siracusa, Joseph M. (Oxford : Oxford University Press, 2020)
Nuclear Weapons are the most deadly weapon ever invented. This introduction discusses the history and politics of nuclear weapons since their development in the 1940s. It describes the successes and failures of treaties that have aimed for their control and reduction, and their impact on international relations today.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 7, 2020).
Keywords: Nuclear weapons; Nuclear warfare